95.4k views
3 votes
Solve for X in the equation, where 4B = −2X − 2A

Solve for X in the equation, where 4B = −2X − 2A-example-1

1 Answer

2 votes

Answer:

X =
\left[\begin{array}{ccc}2&-7&3\\13&0&2\end{array}\right]

Explanation:

4B = -2X - 2A

Dividing both sides by -2

=> -2B = X + A

Subtracting A to both sides

=> X = -2B-A

Now, Let's Solve:

=> X =
-2\left[\begin{array}{ccc}0&2&-2\\5&0&3\end{array}\right] -\left[\begin{array}{ccc}-2&3&1\\-3&0&4\end{array}\right]

=> X =
\left[\begin{array}{ccc}-2*0&-2*2&-2*-2\\-2*5&-2*0&-2*3\end{array}\right] - \left[\begin{array}{ccc}-2&3&1\\-3&0&4\end{array}\right]

=> X =
\left[\begin{array}{ccc}0&-4&4\\10&0&6\end{array}\right] - \left[\begin{array}{ccc}-2&3&1\\-3&0&4\end{array}\right]

=> X =
\left[\begin{array}{ccc}0-(-2)&-4-3&4-1\\10-(-3)&0-0&6-4\end{array}\right]

=> X =
\left[\begin{array}{ccc}2&-7&3\\13&0&2\end{array}\right]

User Joshua Karanja
by
5.8k points